Use of a GP-endorsed 12 months' reminder letter to promote uptake of bowel scope screening: protocol for a randomised controlled trial in a hard-to-reach population. Issue 5 (5th May 2018) - von Wagner, Christian; Hirst, Yasemin; Tookey, Sara; Kerrison, Robert S.; Marshall, Sarah; Prentice, Andrew; Vulkan, Daniel; Macleod, Una; Duffy, Stephen
Abstract : Introduction: Flexible sigmoidoscopy (FS) screening is associated with reduced colorectal cancer incidence and mortality when offered as a one-off test to men and women aged 55–64. The test, also referred to as the 'bowel scope screening' (BSS) test, was added to England's national Bowel Cancer Screening Programme in March 2013, where it is offered to men and women aged 55. Since its implementation, uptake of the BSS test has been low, with only 43% of the eligible population attending an appointment. Sending non-participants a reminder at age 56 has been shown to improve uptake by up to nine percentage points at a single centre in London; we hypothesise that adding a general practitioners (GPs) endorsement to the reminder could improve uptake even further. Methods and analysis: This paper describes the protocol for a randomised controlled trial which will examine the effectiveness of adding a GPs endorsement to a reminder for BSS non-participants aged 56. All screening-eligible adults who have not responded to a BSS appointment at London North West Healthcare NHS Trust within 12 months of their initial invitation will be randomised to receive either a GP-endorsed reminder letter or reminder letter without GP endorsement. The primary outcome will be the proportion of individuals screened within each group 8 weeks after the reminder. Statistical comparisons will be made using univariate and multivariate logistic regression, with 'uptake' as the outcome variable, GP reminder group as the exposure and sociodemographic variables as covariates. Ethics and dissemination: The study was approved by the Yorkshire & Humber—Bradford Leeds Research Ethics Committee (16/YH/0298) and the Confidentiality Advisory Group (17/CAG/0162). The results will be disseminated in a peer-reviewed journal in accordance with the Consort statement and will be made available to the public. Trial registration number: ISRCTN82867861